CRIMINAL POLICY OF SOCIAL WORKERS IN THE FRAMEWORK OF COMPLETING OVER CAPACITIES CORRECTIONAL INSTITUTIONS - Wahyu Satriyo; Slamet Widodo (UNES Law Review, 2023)
The politics of criminal law is related to the legal policy of imposing criminal sanctions on social workers which is currently a common problem. The imposition of these sanctions causes over capacities which results in the loss of the function and objectives of Correctional Institutions as fostering and protecting institutions, while research methods use normative juridical approaches using conceptual and statutory approaches. The conclusion is that the policy of imposing criminal penalties on social workers is appropriate in order to reduce over capacities. Recommendations need for legality in the form of a ministerial decree regarding the imposition of a criminal case for social workers.